CONTRIBUTION OF THE SCIENTIFIC CENTRE OF CHILDREN HEALTH OF THE RUSSIAN ACADEMY OF MEDICAL SCIENCES TO DEVELOPMENT OF SOCIAL PEDIATRICS - V. Yu. Al'bitskii; S. A. Sher; N. V. Ustinova ("Paediatrician" Publishers LLC, 2013)
This article is dedicated to the contribution of the fellow workers of the Scientific Centre of Children Health of the Russian Academy of Medical Sciences to development of Russian social paediatrics. This article shows the distinguished roles of doctors and scientists of the center in the development of social paediatrics as both a science and practice, throughout its 250-years history beginning from the creation of the Imperial Foundling Hospital and until the present day. Owing to the great activity of paediatricians and research workers, a centre and a scientific school of social pediatrics were formed in the Scientific Centre of Children Health.